Novel CCL3-HMGB1 signaling axis regulating osteocyte RANKL expression in multiple myeloma - Aric Anloague; Hayley M. Sabol; Japneet Kaur; Sharmin Khan; Cody Ashby; Carolina Schinke; C. Lowry Barnes; Farah Alturkmani; Elena Ambrogini; Michael Tveden Gundesen; Thomas Lund; Anne Kristine Amstrup; et al. (Haematologica)
Multiple myeloma (MM) is a clonal plasma cell proliferative malignancy characterized by a debilitating bone disease. Osteolytic destruction, a hallmark of MM, is driven by increased osteoclast number and exacerbated bone resorption, primarily fueled by the excessive production of RANKL, the master regulator of osteoclast formation, within the tumor niche. We previously reported that osteocytes, the most abundant cells in the bone niche, promote tumor progression and support MM bone disease by overproducing RANKL. However, the molecular mechanisms underlying RANKL dysregulation in osteocytes in the context of MM bone disease are not entirely understood. Here, we present evidence that MM-derived CCL3 induces upregulation of RANKL expression in both human and murine osteocytes. Through a combination of in vitro, ex vivo, and in vivo models and clinical data, we demonstrate that genetic or pharmacologic inhibition of CCL3 prevents RANKL upregulation in osteocytes and attenuates the bone loss induced by MM cells. Mechanistic studies revealed that MM-derived CCL3 triggers the secretion of HMGB1 by osteocytes, a process required for osteocytic RANKL upregulation by MM cells. These findings identify a previously unknown CCL3-HMGB1 signaling axis in the MM tumor niche that drives bone resorption by promoting RANKL overproduction in osteocytes.